Legal monism : law, philosophy, and politics - Gragl, Paul (Oxford : Oxford University Press, 2018)
In this full-length study of legal monism, Paul Gragl advocates for the revival of legal monism as a solution to normative conflicts between different bodies of law. Using comprehensive and inter-disciplinary arguments, this text defends the theory against dualism and pluralism.
This edition previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on April 19, 2018).
Keywords: International law -- Philosophy; Law; International law